Designing a Process Model for Premarital Counseling - Bateni Noshabadi, Reyhaneh; Mohammadi, Hamed; Aynechi, Abbas (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to design a culturally grounded and scientifically validated process model for premarital counseling tailored to the sociocultural context of Iran. Methods and Materials: The research employed a qualitative methodology using the Delphi technique combined with thematic analysis and SWOT analysis to collect and analyze expert opinions. Twelve professionals—including psychologists, counselors, and executives in family-related institutions—were selected through purposive sampling. Data were gathered via semi-structured interviews, then coded and categorized into organizing and overarching themes. The resulting model was structured across five stages (education and awareness, psychological assessment, counseling interventions, post-marital follow-up, and final evaluation) and three functional levels (individual, interpersonal, and institutional). Findings: The data analysis yielded four overarching themes: (1) coherence and systematization of the counseling process, (2) the role of culture, family, and social factors, (3) quality, tools, and scientific standards, and (4) training of communication, cognitive, and emotional skills. Participants emphasized the lack of standardized national frameworks, the influence of cultural and familial values on counseling receptivity, and the need for technological innovation in service delivery. The proposed model integrated these insights by offering a staged, interdisciplinary, and culturally responsive counseling structure that bridges psychological rigor with institutional coordination. Conclusion: The developed model provides a comprehensive framework for premarital counseling that addresses both micro-level relational dynamics and macro-level systemic gaps. Its emphasis on cultural adaptability, psychological assessment, counselor training, and digital integration makes it a viable blueprint for enhancing counseling practices in Iran and similar contexts.